Joseph Aloysius Hansom (1803-82): His Yorkshire Works, Patronage and Contribution to the Catholic Revival. (1st August 2013) - Harris, Penelope
Abstract : The York origins of the Roman Catholic architect Joseph Aloysius Hansom have largely been overlooked. Here, their significance is presented in a fresh perspective. Hansom was born in Micklegate, York, at the heart of a thriving Catholic community, and through his grandmother's home parish of Everingham gained access to influential Catholic families. His immediate family comprised several generations of builders, while the period into which he was born — which saw the aftermath of the French revolution, an influx of Irish immigrants, and rapid industrial and urban growth, together with the Gothic Revival and the Catholic Revival — gave every opportunity for a talented and entrepreneurial architect to make his mark. To these are added Hansom's flair for generating and maintaining personal contacts, the foundation upon which his success was based. A summary of his main work across the county shows how his career developed and highlights the rich diversity of his work.